2020
DOI: 10.1111/jcmm.15505
|View full text |Cite
|
Sign up to set email alerts
|

Asiaticoside might attenuate bleomycin‐induced pulmonary fibrosis by activating cAMP and Rap1 signalling pathway assisted by A2AR

Abstract: Asiaticoside (AS) has been reported to have protective effect on pulmonary fibrosis (PF). In this study, we aimed to explore the potential mechanism of the therapeutic role of AS and its relationship with A2AR in PF. Adenosine 2A receptor gene knockout (A2AR −/− ) mice and wild‐type (WT) mice were used to establish bleomycin (BLM)‐induced PF models and were then treated with AS (50 mg/kg/d). Pulmonary inflammation and fibrosis were observed in the PF model with much higher severity in A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…AS could induce type-I collagen synthesis to promote the repair of skin (8). Extensive pharmacological research have demonstrated that AS exerts anti-inflammatory (9), anti-tumor (10), antioxidant (11), and anti-fibrosis (12) effects, among others. The latest research showed the protective effect of AS against cerebral I/R injury via downregulating the NOD2/ MAPK/NF-κB pathway in rats (13).…”
Section: Introductionmentioning
confidence: 99%
“…AS could induce type-I collagen synthesis to promote the repair of skin (8). Extensive pharmacological research have demonstrated that AS exerts anti-inflammatory (9), anti-tumor (10), antioxidant (11), and anti-fibrosis (12) effects, among others. The latest research showed the protective effect of AS against cerebral I/R injury via downregulating the NOD2/ MAPK/NF-κB pathway in rats (13).…”
Section: Introductionmentioning
confidence: 99%
“…As a key pathway, Rap1 signaling pathway is related to respiratory system, cardiovascular system, and nervous system sequelae. Some experiments have confirmed that drugs can activate the Rap1 signaling pathway to restrict blood vessel formation and improve the symptoms of pulmonary fibrosis by regulating genes related to the Rap1 signaling pathway [ 156 , 157 ]. The Rap1 signaling pathway can regulate the differentiation of bone marrow mesenchymal stem cells and play a role in the treatment of cardiovascular diseases [ 158 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipid signaling has been shown to regulate a variety of cellular processes and has been implicated in collagen gene regulation 28 .Previous studies improved the glycerophospholipid metabolism can ameliorate liver brosis 29 . The Epac1/Rap1 pathway contributed to the main effect of cAMP on renal brosis 30,31 . Correlation analysis between transcriptomics and proteomics showed signi cant pathway was longevity regulating pathway-worm and FoxO signaling pathway.…”
Section: Discussionmentioning
confidence: 99%